Prevalence and impact of TWILIGHT criteria in all-comer patients undergoing percutaneous coronary intervention. (3rd October 2022) - Spirito, A; Koh, W J; Sartori, S; Snyder, C; Nicholas, J; Cao, D; Vogel, B; Rezvanizadeh, V; Jones, D; Baber, U; Sweeny, J; Sharma, S; et al.
Abstract: Background: The Ticagrelor with Aspirin or Alone in High-Risk Patients after Coronary Intervention (TWILIGHT) randomized clinical trial demonstrated that in selected high risk patients who took ticagrelor and aspirin for 3 months after percutaneous coronary intervention (PCI), continuing ticagrelor alone was associated with significantly less bleeding events than ticagrelor plus aspirin and did not lead to ischemic harm over a period of 1 year (1). The prevalence and risk of adverse events of patients fulfilling the TWILIGHT inclusion criteria in real-world setting is unclear. Purpose: To elucidate the prevalence and prognosis of patients fulfilling the TWILIGHT inclusion criteria. Methods: Patients that received at least one drug eluting stent in a coronary artery at a large tertiary center (Mount Sinai Hospital, New York) were considered for inclusion. As in the TWILIGHT trial, individuals on chronic oral anticoagulation treatment, with STEMI, cardiogenic shock, on dialysis, with prior stroke, or platelet count <100, 000 were excluded. Patients were stratified in two groups: 1) TWILIGHT-like patients, who met at least one clinical (age ≥65 years, female sex, established vascular disease, diabetes mellitus, estimated glomerular fraction rate <60mL/min, acute coronary syndrome with troponin increase) and one angiographic (multivessel coronary artery disease [CAD], stent length >30mm, thrombotic target lesion, bifurcation requiring 2 stents, left main or proximal left anterior descending artery lesion, atherectomy device use, SYNTAX score ≥23) TWILIGHT inclusion criterion; 2) Non-TWILIGHT-like patients, who did not fulfil at least one clinical and one angiographic TWILIGHT inclusion criterion. The primary outcome was a composite of death, myocardial infarction (MI), stroke. Secondary outcomes included bleeding, components of the primary outcome, target vessel and target lesion revascularization, stent thrombosis. All events were assessed at 1 year after PCI. Results: Out of 30, 470 patients undergoing PCI between 2012 and 2019, 13, 236 were included in the current analysis. TWILIGHT criteria were met in 11, 018 (83%) patients. Established vascular disease and multivessel CAD were the most frequently fulfilled criteria. At 1 year, TWILIGHT-like patients were at higher risk for the primary outcome (3.2% vs 1.1%, HR 2.85, 95% CI 1.83–4.44), severe bleeding (3.3% vs 1.8%, HR 1.86, 95% CI 1.32–2.62), all-cause death (1.4% vs 0.4%, HR 3.63, 95% CI 1.70–7.77), myocardial infarction (1.8% vs 0.6%, HR 2.81 95% CI 1.56–5.04), TVR (7.8% vs 4.1%, HR 1.94, 95% CI 1.53–2.47), TLR (5.1% vs 1.7%, HR 2.98 95% CI 2.07–4.29). Stent thrombosis and stroke rate were generally low and did not differ between patients meeting or not the TWILIGHT inclusion criteria. Conclusion: Among all-comer patients undergoing PCI, the fulfillment of the TWILIGHT inclusion criteria is frequent and is associated with a higher risk of death, ischemic and bleeding complications Funding Acknowledgement: Type of funding sources: None.